A water-dependent kinetics guide for complex lipase-mediated synthesis of biolubricants in a water activity control reactor. Issue 12 (1st September 2015) - Tao, Yifeng; Chen, Guohua; Pavlidis, Ioannis V.; Jiang, Yang; Qie, Longfei; Cui, Caixia; Liu, Luo; Chen, Biqiang; Tan, Tianwei
Abstract : A water-dependent kinetic model for a lipase-mediated reaction with multiple substrates and products in a water activity control reactor was developed. Abstract : A water-dependent kinetic model for a lipase-mediated reaction with multiple substrates and products in a water activity control reactor was developed. Solvent-free esterification of trimethylolpropane (TMP), the products of which can be used as biolubricants, was investigated using a lipase from Candida sp. 99–125 as catalyst under variable water activities in a 5 L batch stirred tank reactor. Water activity control was accomplished at the set point by introduction of dry air through the reaction medium at a digital feedback-controlled flow rate. For the cases of esterification of TMP, long-term (>72 h) control of water activity resulted in a considerable improvement of yield. By introducing progressive water removal and combining principles with an intrinsic kinetic model of the Ping-Pong Bi-Bi mechanism, the integrated model can predict both the forward and reverse rates for TMP reactions. Kinetic parameters depending on the water activity were estimated by nonlinear regression fitting of experimental data. The proposed approach not only enables optimization of the reaction under defined conditions, but also provides a solution for industrial upscaling of similar environmentally friendly biocatalytic processes.